Trade-offs in Bank Resolution - Dell'Ariccia, Giovanni (Staff Discussion Notes; Staff Discussion Notes ;, 2018)
This SDN revisits the debate on bank resolution regimes, first by presenting a simple model of bank insolvency that transparently describes the trade-off involved between bail-outs, bail-ins, and larger capital buffers. The note then looks for empirical evidence to assess the moral hazard consequences of bail-outs and the systemic spillovers from bail-ins.